Clinical Correlates of Health-Related Quality of Life in Adults With Chronic Tic Disorder - Isaacs, David A.; Riordan, Heather R.; Claassen, Daniel O. (Frontiers in Psychiatry, 2021)
Tics are the hallmark feature of Tourette syndrome (TS), but psychiatric and sensory symptoms are widely prevalent and increasingly recognized as core manifestations of the disorder. Accumulating evidence suggests that these psychiatric and sensory symptoms exert greater influence on quality of life (QOL) than tics themselves. However, much remains uncertain about determinants of QOL in TS due to the complexity of the clinical presentation. Here, we sought to clarify the association between health-related QOL (HRQOL) and common psychiatric and sensory symptoms in adults with TS and other chronic tic disorders. To do so, we prospectively recruited 52 patients from a tertiary care clinic to complete self-report measures assessing HRQOL (Gilles de la Tourette-Quality of Life Scale, GTS-QOL), depression (Patient Health Questionnaire-9, PHQ-9), anxiety (Generalized Anxiety Disorder Scale-7, GAD-7), obsessive-compulsive symptoms (Dimensional Obsessive-Compulsive Scale, DOCS), attention deficit hyperactivity disorder symptoms (Adult ADHD Self-Report Screening Scale for DSM-5, ASRS-V), and premonitory urge (Premonitory Urge to Tic Scale, PUTS). All participants were also administered the Yale Global Tic Severity Scale (YGTSS) to quantify tic severity. Using correlational analysis and multivariable linear regression modeling, we found that GTS-QOL score was significantly associated with scores from all other rating scales, with the exception of the PUTS. GTS-QOL was most strongly associated with PHQ-9, followed by ASRS-V, GAD-7, DOCS, and YGTSS total tic score. The regression model including these five independent variables, as well as sex, explained 79% of GTS-QOL score variance (F(6,40)=29.6, p<0.001). Specific psychiatric symptoms differentially impacted physical, psychological, and cognitive HRQOL. Systematic assessment of psychiatric comorbidities is imperative for clinical care and clinical research efforts directed at improving QOL in adults with chronic tic disorders.